Beauty Hunkering Memory - Kilates, Marne (Likhaan: The Journal of Contemporary Philippine Literature, 2010)
At the Carenderia Tampuhan Hidalgo's Vendadora Recollections of Paradise The Huntress by Bencab Delotavo's Diaspora Junkscape